Highly crystallized α-FeOOH for a stable and efficient oxygen evolution reaction. Issue 5 (9th January 2017) - Luo, Wenjun; Jiang, Chaoran; Li, Yaomin; Shevlin, Stephen A.; Han, Xiaoyu; Qiu, Kaipei; Cheng, Yingchun; Guo, Zhengxiao; Huang, Wei; Tang, Junwang
Abstract : A well-crystallized α-FeOOH (a goethite widespread in nature) shows an efficient and stable oxygen evolution reaction by removing surface chemically adsorbed water. Abstract : It is a key challenge to explore an efficient, stable and low-cost catalyst for the oxygen evolution reaction (OER). Herein, we show a facile strategy to significantly enhance the electrocatalytic activity and stability of crystalline α-FeOOH by rapid heat treatment. We identify that crystalline α-FeOOH shows not only electrocatalytic activity as high as the benchmark FeOOH catalyst (amorphous γ-FeOOH), but also the highest stability among all FeOOH electrocatalysts for the OER in alkaline solutions. Our findings not only deepen the fundamental understanding of the OER process on these materials but also guide further development of new low-cost electrocatalysts for energy storage via water splitting.